Folic acid-functionalized drug delivery platform of resveratrol based on Pluronic 127/D-α-tocopheryl polyethylene glycol 1000 succinate mixed micelles - Hao J (Dove Medical Press, 2017)
Jifu Hao,* Tiantian Tong,* Kai Jin, Qiannan Zhuang, Te Han, Yanping Bi, Jianzhu Wang, Xiaodan Wang College of Pharmacy, Taishan Medical University, Taian, People’s Republic of China *These authors contributed equally to this work Abstract: A folic acid (FA)-functionalized drug vehicle platform based on Pluronic 127 (P127)/D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) mixed micelles was orchestrated for an effective delivery of the model drug resveratrol in order to address the problem of poor water solubility and rapid metabolism of resveratrol and improve its targeted accumulation at tumor site. The FA-decorated mixed micelles were prepared using thin-film hydration method and optimized by central composite design approach. The micelles were also characterized in terms of size and morphology, drug entrapment efficiency and in vitro release profile. In addition, the cytotoxicity and cell uptake of the micelles were evaluated in folate receptor-overexpressing MCF-7 cell line. In vivo pharmacokinetic and biodistribution studies were also performed. The average size of the micelles was ~20 nm with a spherical shape and high encapsulation efficiency (99.67%). The results of fluorescence microscopy confirmed the targeting capability of FA-conjugated micelles in MCF-7 cells. FA-modified micelles exhibited superior pharmacokinetics in comparison with that of solution. Further, the low accumulation of resveratrol-loaded FA micelles formulation in the heart and kidney avoided toxicity of these vital organs. It could be concluded that folate-modified P127/TPGS mixed micelles might serve as a potential delivery platform for resveratrol. Keywords: resveratrol, Pluronic 127/TPGS, mixed micelles, folic acid conjugation